Pelatihan Pengembangan Assesmen Berbasis Digital Dalam Aspek Perkembangan Anak Usia Dini - Sofya, Rani; Mahyuddin, Nenny; Damanik, Enceria; Aprihatin, Yessy (Universitas Negeri Padang, 2025)
TK Latihan SPG Aisyiyah has not fully integrated digital technology into its assessment process, even though in this era, it is essential to do so that it can improve the quality and effectiveness of the assessment. This community service aims to improve teacher skills in developing digital assessments and improve the quality of learning at TK Latihan SPG Aisyiyah. This community service has improved teachers' ability to produce digital assessments. This can be seen from the increase in teacher understanding in the post-test, with an average score of 89 and an increase in the pre-test score of 83.25. In addition, 100% of kindergarten teachers who participated in the training also produced digital assessments afterwards. The satisfaction questionnaire results showed that participants were delighted with implementing community service activities, with an average satisfaction level of 94%. Participants hope that similar training can be carried out again further to improve the competence of early childhood education teachers.